‘I am not complete without my family’: a culture-centred exploration of meanings of health and well-being among migrant Indian nurses in Aotearoa New Zealand - Jayan P; Dutta MJ; Thaker J (Taylor and Francis Group on behalf of the Australian and Aotearoa New Zealand Communication Association (AANZCA), 2025)
In Aotearoa New Zealand, the voices of migrant nurses are often overlooked and marginalised despite being visible in the economy. This manuscript uses a culture-centred approach to centre the voices of migrant Indian nurses on understanding their meanings of health and well-being. Contrary to the Western models, which position health as individual accountability, the thirty in-depth conversations with migrant Indian nurses point towards the importance of collective in maintaining health and well-being. The dialogues with participants revealed three main themes: the family and community as interwoven to health and well-being, migration and the hidden health cost of family disconnection, and the significance of culturally appropriate food in maintaining health. This study contributes to health communication theory and practice by providing insights into the health and well-being meanings of migrant nurses, centring their voices as replacements to neoliberal, dominant paradigms of health.
Keywords: Migrants; New Zealand; health communication; nurses